Lingga Yoni site in Tasikmalaya: Overlooked Educational Potential Amidst the Threat of Exploitation of Nature - Hamdani, Reza Renggana; Yuliantri, Rhoma Dwi Aria; Firdaus, Dede Wahyu (Universitas Negeri Padang, 2025)
The Lingga Yoni Indihiang site in Tasikmalaya is a cultural remnant of the Hindu-Buddhist period that has high historical, spiritual, and archaeological value. Based on the results of excavations and carbon tests, the site is estimated to date back to the 7th century AD. This research is motivated by a number of problems, including the threat of environmental exploitation due to sand and asphalt mining activities adjacent to the site, the problem of access to land controlled by the private sector, and the low use of the site as a medium for learning history. These problems are exacerbated by the lack of publications, the lack of supporting facilities, ownership conflicts, and differences in religious views of the surrounding community. This study uses a descriptive qualitative method with a case study approach. Data collection techniques are carried out through field observations, interviews with stakeholders (site managers, surrounding communities, and related agencies), and documentation studies of relevant literature and archives. The research location focuses on the Lingga Yoni site area in the Indihiang District, Tasikmalaya City. The results of the discussion show that although there have been physical preservation measures, such as the installation of fences, these efforts have not addressed the structural challenges faced by the site. A participatory-based preservation strategy is needed that involves the active role of the community, educational institutions, and the government collaboratively. The conclusion of this study emphasises the importance of integrated site management so that Lingga Yoni Indihiang can function optimally as a protected cultural heritage as well as a means of education and local identity of Tasikmalaya. encouraging students to think critically and gain a deeper understanding of history.